Optical measurements of microrheological parameters of blood and analysis of their relationship with its viscosity in cardiovascular diseases - Umerenkov, Danila Alekseevich; Ermolinskiy, Petr B.; Lugovtsov, Andrei Egorovich; Dyachuk, Larisa I.; Priezzhev, Alexander Vasil'evich (Известия Саратовского университета. Новая серия Серия: Физика)
Background and Objectives: Blood plays a key role in supplying oxygen to the body tissues and transporting various substances throughout the body. Thus, the parameters characterizing blood flow reflect the quality of blood functionality. Current research assumes that microrheological changes, including the properties of red blood cells and platelets, may play an important role in the development and progression of CVD. Changes in these parameters can lead to disturbances in blood circulation, contributing to the development and progression of atrial fibrillation. This emphasizes the need for an integrated approach to studying the relationship between blood viscosity and microrheology and the functional status of patients with CVD. Understanding this relationship can help in the development of new methods for diagnosing and treating CVD and other socially significant and age-associated diseases. Materials and Methods: Whole blood viscosity measurements were performed on a Lamy Rheology RM100 CP1000 rotational viscometer. Quantitative assessment of erythrocyte aggregation was carried out using the diffuse light scattering method implemented in the RheoScan-AnD300 device. The deformability of erythrocytes was measured using the laser ektacytometry method, which is also implemented in the RheoScan device. The parameters of platelet aggregation kinetics were assessed from the light scattering signal from a suspension of these cells using an ALAT-2 laser platelet aggregation analyzer. Results: It has been shown that in patients with various cardiovascular diseases the relationship between the viscosity of whole blood and the microrheological parameters that characterize it is altered. Moreover, this relationship is expressed differently in different groups of patients depending on the concrete type of CVD. It has also been found that the relationship between blood viscosity and blood microrheological parameters becomes less pronounced for patients with CVD compared to the control group of healthy individuals. Conclusion: This paper examines the correlations between the whole blood viscosity and the microrheological parameters of blood for patients with CVD. The obtained results contribute to better understanding and demonstrate the relationship between the microrheological parameters of blood and its viscosity, which may be used in clinical studies and to adjust patient treatment protocols after additional statistical validation.